2013
DOI: 10.1016/j.ecoenv.2013.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Health risk implications from simultaneous exposure to multiple environmental contaminants

Abstract: Keywords:Heavy metals Oestradiol Human health Microbial pathogens Water quality abstract Water quality has deteriorated in the upper Olifants River system, South Africa, as a result of land use activities which include mining, agriculture and industries. A health risk assessment was conducted from 2009 to 2011 in the catchment to determine the possible risks local communities face from various pollutants such as microbials, heavy metals and oestrogen in the river water and vegetation. Aluminium and manganese a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 42 publications
1
25
2
2
Order By: Relevance
“…This emphasizes the need to conduct environmental risk assessments (ERAs) to monitor both influents and effluents of water treatment facilities. Apart from the problem that some WWTWs in South Africa do not comply with water quality standards and service delivery, another problem exists in that untreated river water is also not subjected to such water quality guideline initiatives, as this is not regarded as a drinking water resource in South Africa (Genthe et al, 2013). However, several rural communities depend on water taken directly from rivers for general daily activities, such as washing, cooking and consumption, as well as for agricultural purposes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This emphasizes the need to conduct environmental risk assessments (ERAs) to monitor both influents and effluents of water treatment facilities. Apart from the problem that some WWTWs in South Africa do not comply with water quality standards and service delivery, another problem exists in that untreated river water is also not subjected to such water quality guideline initiatives, as this is not regarded as a drinking water resource in South Africa (Genthe et al, 2013). However, several rural communities depend on water taken directly from rivers for general daily activities, such as washing, cooking and consumption, as well as for agricultural purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental contaminants causing disruption of the reproductive endocrine system have been the focus of many EDC studies around the world, including South Africa, where varying concentrations of contaminants having known oestrogenic endocrine-disrupting effects have been found in surface waters (Aneck-Hahn et al, 2009;Bornman et al, 2007;Slabbert et al, 2007;Genthe et al, 2013). Such studies may be only the tip of the iceberg, as increasing number of ECs are shown to have endocrine-disrupting activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Genthe et al (2013) and Jooste et al (2015) also concur that the Olifants River is one of the most polluted rivers in Southern Africa as a consequence of anthropogenic stressors which include coal mining, coal-fired power generation, chemical manufacturers, chrome and steel smelters, and agriculture and sewage effluents. A study by CSIR (2012) to assess the risk of water pollution in the Upper Olifants River with reference to aquatic ecosystem health and human health concluded that BPollutants from urban-based anthropogenic activities have had significant adverse impacts on the aquatic health of the Olifants River system, causing widespread eutrophication, localised toxic water quality and increased the potential for bioaccumulation of pollutants through the food chain^.…”
Section: Introductionmentioning
confidence: 90%
“…The emergence of visible injurious effects of pollutants on hydrophytes like decreased growth, loss of vitality and leaf damage is usually depended on exposure time and concentration of toxicants (Karatas et al 2009). Genthe et al (2013) examined the metal content of some plants sampled from the Olifants River in South Africa's Mpumalanga Province. Their findings showed an overall increased aluminium (Al) and manganese (Mn) absorption in the plant roots compared to their shoots (relative to control plants).…”
Section: Macrophytesmentioning
confidence: 99%